Nanofiber‐based polymer electrolyte membranes for fuel cells - Ning Liu; Shuguang Bi; Yi Zhang; Ying Ou; Chunli Gong; Jianhua Ran; Yihuang Chen; Yingkui Yang (Carbon Energy)
Abstract Developing low‐cost and high‐performance nanofiber‐based polyelectrolyte membranes for fuel cell applications is a promising solution to energy depletion. Due to the high specific surface area and one‐dimensional long‐range continuous structure of the nanofiber, ion‐charged groups can be induced to form long‐range continuous ion transfer channels in the nanofiber composite membrane, significantly increasing the ion conductivity of the membrane. This review stands apart from previous endeavors by offering a comprehensive overview of the strategies employed over the past decade in utilizing both electrospun and natural nanofibers as key components of proton exchange membranes and anion exchange membranes for fuel cells. Electrospun nanofibers are categorized based on their material properties into two primary groups: (1) ionomer nanofibers, inherently endowed with the ability to conduct H+ (such as perfluorosulfonic acid or sulfonated poly(ether ether ketone)) or OH− (e.g., FAA‐3), and (2) nonionic polymer nanofibers, comprising inert polymers like polyvinylidene difluoride, polytetrafluoroethylene, and polyacrylonitrile. Notably, the latter often necessitates surface modifications to impart ion transport channels, given their inherent proton inertness. Furthermore, this review delves into the recent progress made with three natural nanofibers derived from biodegradable cellulose—cellulose nanocrystals, cellulose nanofibers, and bacterial nanofibers—as crucial elements in polyelectrolyte membranes. The effect of the physical structure of such nanofibers on polyelectrolyte membrane properties is also briefly discussed. Lastly, the review emphasizes the challenges and outlines potential solutions for future research in the field of nanofiber‐based polyelectrolyte membranes, aiming to propel the development of high‐performance polymer electrolyte fuel cells.